A Novel NR5A1 Mutation in a Thai Boy with 46, XY DSD - Wacharasindhu, Suttipong; Ittiwut, Chupong; Ittiwut, Rungnapa; Aroonparkmongkol, Suphab; Suphapeetiporn, Kanya (Journal of Pediatric Genetics, 2023)
Disorders of sex development (DSD) can be classified as 46,XX DSD, 46,XY DSD, and sex chromosome DSD. Several underlying causes including associated genes have been reported. Steroidogenic factor-1 is encoded by the NR5A1 gene, a crucial regulator of steroidogenesis in the growth of the adrenal and gonadal tissues. It has been discovered to be responsible for 10 to 20% of 46, XY DSD cases. Here, we described a 2-month-old infant who had ambiguous genitalia and 46, XY. Using whole exome sequencing followed by polymerase chain reaction–Sanger sequencing, a novel heterozygous nonsense c.1249C > T (p.Gln417Ter) variant in the NR5A1 gene was identified. It is present in his mother but absent in his father and maternal aunt and uncle. At the age of 7 months, the patient received a monthly intramuscular injection of low-dose testosterone for 3 months in a row. His penile length and diameter increased from 1.8 to 3 cm and from 0.8 to 1.3 cm, respectively. The patient also had normal adrenal reserve function by adrenocorticotropic hormone stimulation test. This study identified a novel causative p.Q417X (c.1249C > T) variant in NR5A1 causing 46,XY DSD in a Thai boy which is inherited from his unaffected mother.
Keywords: disorders of sex development; NR5A1; novel; mutation